Le dépôt bimétallique du vie s. av. J.-C. de Tavers (Loiret, région Centre) : présentation liminaire - Pierre-Yves Milcent; Christian Cribellier; Arthur Tramon (Gallia)
A metal deposit from the Early Iron Age has recently been discovered in Tavers. Thanks to a geophysical prospection and a mechanical sounding campaign, we can suppose it was quite isolated. Several centuries after its burying, a large rural establishment during the end of the Iron Age, then a Roman villa succeeded each other next to it. The deposit comprises 65 items, mainly made out of copper alloy and four of them made of iron; the association of these two materials is exceptional in this setting. These items consist mainly of adornments, but there are also some weapons and a series of miniature socketed axes. The composition of this deposit is quite original and seems to cross different cultural traditions. It shows a wide range of metal products in a formerly ill-documented area in this field. The association of these objects allows us to date some products, initially badly dated, from the late 6th c. B.C., including the model Armorican-like axes.